The Effect of Tax Fairness on Tax Compliance with Trust as an Intervening Variable - Muslichah, Muslichah; Graha, Vina Satya (Postgraduate Program Merdeka University, 2018)
The purpose of this study is to provide empirical evidence about the effect of tax fairness on tax compliance with trust to tax authority as an intervening variable.300 questionnaires were distributed, 195 were returned for a response rate of 65 percent. The Partial Least Squares (PLS) approach is used to test the hypotheses developed in this study. SmartPLS software is used for this study.This study reveals four important findings: (1) tax fairness has a significant positive effect on tax compliance, (2) tax fairnessÂ has a significant positive effect on trust, (3) trust has a significant positive effect on tax compliance, (4) trust mediates the relationship between tax fairness and tax compliance.This research not only has implications on practice but also to the literature concerning the effect of tax fairness and truston tax compliance. It is also expected that this research provides valuable information for the government to create a fair tax system.Â DOI: https://doi.org/10.26905/afr.v1i2.2372